New specificity and yield enhancer of polymerase chain reactions - Kovárová, M; Dráber, P (Nucleic acids research, 2000)
Tetramethylammonium (TMA) chloride, dimethyl sulfoxide and formamide are known to increase, under certain conditions, the specificity and efficiency of the polymerase chain reaction (PCR). We compared the ability of several TMA derivatives and some other reagents to increase the specificity of PCR and to improve the yield of amplification. A novel combination of the enhancer TMA and oxalate as anion is demonstrated to be a powerful enhancer of PCR. Addition of 2 mM TMA oxalate to the PCR mixture decreases the formation of non-specific DNA fragments and increases the yield of specific PCR products.
Keywords: krysa rodu Rattus; Animals; indikátory a reagencie; Thy-1 Antigens; zvířata; antigeny Thy-1; Mice; Sensitivity and Specificity; kvartérní amoniové sloučeniny; polymerázová řetězová reakce; Rats; Polymerase Chain Reaction; senzitivita a specificita; Indicators and Reagents; Quaternary Ammonium Compounds; myši